Analisis Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) Pada Proyek Konstruksi Bangunan Bertingkat, Studi Kasus Pembangunan Hotel Di Balige, Toba - Anggun Lady Paska Sibuea; Sandra Aulia Sitompul; Agnes Monaliska Sitanggang; Aldi Harliansyah Harahap; Titonik Feberman Hia; Yuni Yolanda (CV. SINAR HOWUHOWU, 2026)
This study analyzes the implementation of the Occupational Health and Safety Management System (OHSMS/SMK3) at the Hotel XYZ construction project in Balige, Toba, North Sumatra. The project is a 16-story hotel building currently at the structural work stage (floors 6-8) at the time of observation. A qualitative observational method was used, carried out during a 3-month internship period. Data was collected through direct field observations covering risk activities, use of personal protective equipment (PPE), availability of K3 signs and facilities, as well as supervision and work procedures. The results show that high-risk activities such as working at height, heavy equipment operation, material lifting, welding, and electrical work were identified at the site. PPE consisting of safety helmets, reflective vests, safety shoes, work gloves, and full body harnesses were available; however, worker compliance in using PPE was still low. Several critical K3 facilities were not available, including K3 signs, assembly points, fire extinguishers (APAR), Lock Out-Tag Out (LOTO) systems, safety briefings, APD supervision, K3 SOPs, and K3 officers. These findings indicate that the SMK3 implementation at this project is still in the poor category based on the performance criteria of Ministerial Regulation PU No. 9 of 2008. Improvement recommendations include providing complete K3 facilities, implementing routine safety talks, strengthening supervision, and appointing competent K3 officers.